Income limit that separates rural families with and without food security and their determinants in the Andes of Peru, 2015 - Arpi Mayta, Roberto (2017)
The aim of the study is to determine the income limit that separates rural families with and without food security, and to identify the factors that influence in the state of food insecurity of rural families in the Andes of Peru during the year 2015. Using the database of the National Survey of Homes produced by the National Institute of Statistics and Informatics of Peru, the income limit was obtained by estimating the modified Engel curve with two concavities, using the Ordinary Least Squares method; and through a Probit model, the factors influencing the state of food insecurity of rural families were identified. It is concluded that the income limit between families with and without food security is S/ 593.46 per month, which allowed a food expenditure of S/ 356.46 per month. Likewise, the factors that would reduce the state of food insecurity are constituted by: if the head of household is male and married or living together, if there are more household members, if expenditures are allocated to non-food and if they live in the south. While the state of insecurity of families would increase: if the head of household is of age and if he lives in the north sierra. It is recommended to incorporate the income limit that separates families with and without food security and the factors that limit leaving the state of food insecurity of rural families in the design and evaluation of public policies.